(untitled) (Bangladesh Pharmaceutical Journal, 2025)
The diverse biological activities of chalcones and their heterocyclic derivatives have garnered significant attention in the field of medicinal chemistry due to their broad range of pharmacological effects. In this study, the chalcone derivative 1,3-diphenylprop-2-en-1-one (1) was synthesized by the reaction of benzaldehyde and acetophenone in the presence of 40% aqueous sodium hydroxide at room temperature. This intermediate chalcone (1) was then converted into the pyrazoline derivative, 1,3,5-triphenyl-2- pyrazoline (2), through a reaction with phenylhydrazine. In parallel, another reaction of chalcone 1 with guanidine hydrochloride resulted in the formation of a pyrimidine derivative, 4,6-diphenylpyrimidine-2- amine (3). Moreover, phenyl(3-phenyloxiran-2-yl)methanone (4) was synthesized by reacting chalcone 1 with hydrogen peroxide, which was then further subjected to phenylhydrazine to yield 1,3,5-triphenyl- 1H-pyrazol-4-ol (5). All the synthesized compounds were thoroughly characterized using 1H NMR and IR spectroscopy to confirm their chemical structures. To evaluate the potential biological activity of these compounds, their cytotoxicity and antioxidant properties were assessed. The cytotoxicity assay, using HeLa cells, revealed that compounds 1, 3, and 5 exhibited potent antiproliferative effects, with cell survival rates dropping to less than 5%. In parallel, the antioxidant activity was evaluated using the DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging assay, which showed that the compounds exhibited varying levels of antioxidant activity, with IC₅₀ values ranging from 37.30 to 281.76 μg/ml. Additionally, the drug-likeness, physicochemical properties, and pharmacokinetic profiles of these compounds were comprehensively analyzed using the SwissADME web tool, providing valuable insights into their potential for further development as therapeutic agents. Bangladesh Pharmaceutical Journal 28(2): 142-151, 2025 (July)